The RMA methodology at the service of guidance counselling - Sani, Filippo (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
We aim to go more deeply into the process whereby, using a maieutic approach in the management of orientation interviews, it is possible to get on the same wavelength as young people and adults, and address the deeper reasons for their difficulties. As an orientation guide and facilitator, the consultant tries to help the person to equip him/herself cognitively and emotionally to deal with a sustainable – or maieutic – task that can draw the appropriate resources from within the person that are realistically able to face the situation and to find new paths.